The Probability of the Financing Sustainability of Micro-firms Supported by Islamic Social Fund - Andi Hakim; Zuliani Dalimunthe (Faculty of Economic and Business, 2022)
This study aims to identify factors that influence financing sustainability, thereby determining the probability of attaining the subsequent financing from Islamic social funds. Islamic social funds provide funding for micro-firms using a financing scheme that differs from conventional financing terms. For the lower level, Islamic social funds usually offer a limited amount of no-cost financing called qard. In contrast, for more profitable micro-firms, Islamic social funds provide low-cost financing called murabahah. However, most micro-firms need financing in sustainable terms, either using a qard scheme or a murabahah scheme. We assume that only micro-firms showing business growth may generate higher financing using the murabahah scheme. We use data from 1,346 micro-firms. We found several factors that contribute significantly to a micro-firm having a higher chance of generating further funding, such as group-type financing, amount of funding (plafond), time to maturity, and demographic aspects such as age and number of dependents. However, we found that the initial contract scheme. How to Cite:Hakim, A. & Dalimunthe, Z. (2022). The Probability of Financing Sustainability of Micro firms Financially Supported by Islamic Social Fund. Etikonomi, 21(1), 127-138. https://doi.org/10.15408/etk.v21i1.12316.